Analysis of the Accounting Treatment of Grant Funds at the National Unity and Political Agency of Southeast Minahasa Regency - Hosang, Mauren; Laihad, Hendrik; korompis, Claudia WM (ACCOUNTABILITY, 2024)
Grant funds are a form of state responsibility for the provision of social services and welfare. Government grant funds go through budgeting, distribution and reporting stages. This research is to analyze the process and accounting treatment of grant funds at the Southeast Minahasa Regency National and Political Unity Agency. This study used descriptive qualitative method. The results of the research show that the accounting treatment of grant funds at the Southeast Minahasa Regency National and Political Unity Agency was declared to be in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards. The process of budgeting, distributing and reporting grant funds is in accordance with applicable regulations and there are several stages that must be passed so that the grant funds can be disbursed until they are accounted for. Indeed, there are obstacles in the process of accountability for grant funds by grant recipients, but this can still be adjusted. Keywords: Grants, Accounting Treatment